2020
DOI: 10.1021/acsami.0c14447
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Saturable Absorption and Reverse Saturable Absorption in a PEDOT:PSS Film via Electrical Modulation

Abstract: The electrical tuning of the nonlinear absorption of materials has promising application potential, while studies remain rare. In this work, we show that the third-order nonlinear absorption of poly(3,4-ethylenedioxythiophene) chemically doped with poly(styrene sulfonic acid) [PEDOT:PSS] can be effectively modulated by external voltage. The 2 nonlinear absorption of the film can be varied between reverse saturable absorption (RSA) and saturable absorption (SA) via voltage control with laser excitation at 800 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 61 publications
3
10
0
Order By: Relevance
“…The repetition rate of the ns laser is 10 Hz. Open-aperture Z-scan data were fitted by the following expression: 38,39 Close-aperture Z-scan data were fitted by the following expression: 38 where T ( Z ) is the normalized transmittance of the sample, β represents the NLO absorption coefficient, n 2 is the nonlinear refractive index, I 0 is the on-focus laser intensity, and Z 0 is the Rayleigh length ( Z 0 = π ω 0 2 / λ , ω 0 and λ are the waist radius of the lens and the laser wavelength, respectively). L eff = [1 − exp(− α 0 L )]/ α 0 is the effective length of the sample, α 0 represents the linear absorption coefficient, and L is the thickness of the sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The repetition rate of the ns laser is 10 Hz. Open-aperture Z-scan data were fitted by the following expression: 38,39 Close-aperture Z-scan data were fitted by the following expression: 38 where T ( Z ) is the normalized transmittance of the sample, β represents the NLO absorption coefficient, n 2 is the nonlinear refractive index, I 0 is the on-focus laser intensity, and Z 0 is the Rayleigh length ( Z 0 = π ω 0 2 / λ , ω 0 and λ are the waist radius of the lens and the laser wavelength, respectively). L eff = [1 − exp(− α 0 L )]/ α 0 is the effective length of the sample, α 0 represents the linear absorption coefficient, and L is the thickness of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…The repetition rate of the ns laser is 10 Hz. Open-aperture Z-scan data were fitted by the following expression: 38,39 TðZÞ ¼ ln 1þq 0 ðZÞ ½ q 0 ðZÞ (1)…”
Section: Z-scan Measurementsmentioning
confidence: 99%
“…With the addition of PEG, the absorption of the PEDOT film increased gradually above 1200 nm and the intensity of the broad signal at 900-1000 nm was reduced, which indicated the polaron energy level gradually changed to the bipolaron state and the oxidation level of PEDOT increased. 52,53 We observed that the Raman and UV-Vis-NIR spectra of 12-PEDOT showed information that did not match the film conductivity. According to the research by Fabretto et al, 46 the substantial increase of the square resistance and reduction in conductivity at high PEG loading should be due to the steric hindrance of the surfactant acting to insulate individual PEDOT grains.…”
Section: Resultsmentioning
confidence: 96%
“…The SA effect can be applied to Q-switch or passive mode locking techniques to produce short laser pulses, while the RSA effect can be widely used in optical amplitude limiting devices, and plays a protective role for eyes or sensors. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] The SA and RSA responses are influenced by high-intensity light fields and have a dependence on the intrinsic characteristics of the optical materials. Therefore, it is an important challenge to design and synthesize novel third-order nonlinear optical materials to realize SA and RSA response conversion.…”
Section: Introductionmentioning
confidence: 99%